Subject in the work of Michel Foucault – the reflexive subject and governmentality theory - Urošević, Milan A (Sociološki pregled, 2020)
By examining Foucault’s understanding of the subject we will try to answer whether his work is better viewed as a form of theoretical continuity or discontinuity. We begin by elaborating his basic theoretical notions. After that we analyze the relationship between the subject and government in the second period of his work. We continue by analyzing the relationship between the subject and government through the notion of the “government by the truth” which he introduces in his third period. The last chapter deals with some contradictions of Foucault’s understanding of the subject in his third period. We conclude by stating that Foucault’s work overcomes the traditional sociological divide between the micro and the macro levels of the social world.
Keywords: Michel Foucault; subjectivity; reflexivity; the self; government